This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: 28 NHAN LEVAN WEEK 7 RECAP 20. Mean (Least) Square Error M(L)SE 20.1. Parsevals Relation. 1 T T 2 T 2  f ( t )  2 dt = n =  F n  2 . 20.2. A Simple Problem: Estimating the Length of a Tree. A tall tree is represented by a vector v in R 3 . Moreover, we know that v admits the orthonormal representation (20.1) v = i + j + k where (20.2) := v, i , := v, j , and := v, k and i, j, k are orthonormal vectors on the x , y , z , axes respectively. Our problem is to measure the length (or the norm)  v  of v . However, due to the wind and since one gets pain in the neck for looking up for a long time, we cannot get the true value of  v  even after 102 measurements! Because of the above reasons, we turn to the problem of finding a vector v in the x yplane, i.e., R 2 (hence no need to look up, hence no pain in the neck) so that the norm of the error vector (20.3) e := v v is smallest. It is clear that the length of e , denoted by (20.4) E :=  e  =  v v  is simply the length of the vector P P connecting the tip P of v and the tip P of v . In other words (20.5) e := P P and E =  P P  =  e  Now, since v x yplane, it can be represented by (20.6) v = i + j where and are real numbers yet to be determined. It follows from the above setup that our problem is simply to determine and so that the length E of the error vector e is smallest. Another way of saying this is: to minimize the quantity (20.7) E :=  e  =  v v  over all v i.e., all vectors in the x yplane . However, we know that the norm  w  of a vector w is defined as (20.8)  w  := w, w  w  2 = w, w Therefore, instead of minimizing E we can also minimize (20.9) E 2 =  v v  2 = v v, v v 29 An advantage of this is the fact that we can open up the RHS to obtain E 2 = v, v v, v v, v + v, v (20.10) =  v  2 2 v, v +  v  2 (20.11) keeping in mind that since we are dealing with real scalars: v, v = v, v But we know that  v  2 = 2 + 2 + 2 (20.12)  v  2 = 2 + 2 (20.13) v, v = ( i + j + k ) , ( i + j + 0 k ) (20.14) = + (20.15) Therefore (20.11) becomes: E 2 =  v  2 2 v, v +  v  2 (20.16) = ( 2 + 2 + 2 ) 2( + ) + ( 2 + 2 ) (20.17) =...
View
Full
Document
This note was uploaded on 04/01/2008 for the course EE 102 taught by Professor Levan during the Spring '08 term at UCLA.
 Spring '08
 Levan

Click to edit the document details